The incidence and clinical outcomes of postextubation dysphagia in a regional critical care setting. Issue 2 (March 2022) - McInytre, Melanie; Doeltgen, Sebastian; Shao, Ceilia; Chimunda, Timothy
Abstract: Background: Postextubation dysphagia (PED) has been shown to occur in 41% of critically ill patients requiring endotracheal intubation. With one-third of patients with PED experiencing silent aspiration, it is reasonable to anticipate negative health outcomes are likely, although this has not yet been systematically explored in an Australian context. Objectives: The aim of the study was to determine the impact of PED, in a regional Australian intensive care unit (ICU), on rates of pneumonia, the length of stay in the ICU and hospital, and healthcare expenditure. Methods: This study was conducted as a retrospective cohort analysis, which used administrative healthcare data of patients who received endotracheal intubation for invasive mechanical ventilation. Patients with a tracheostomy or known pre-existing dysphagia were excluded. Results: A total of 822 patient episodes were identified, of which 7% (n = 58) presented with PED. Half of all patients within the PED cohort (53%) were intubated for fewer than 48 h. Patients with PED had a longer median length of stay in the ICU (5 days versus 3 days, p < 0.001) and were more likely to develop pneumonia (odds ratio = 2.51, 95% confidence interval = 1.28, 4.95) than extubated patients without dysphagia. Median cost per hospital admission for patients with PED was double that for extubated patients without dysphagia (AUD $42, 685 versus AUD $20, 840, p < 0.001). Conclusions: This study highlights that even a short duration of intubation may carry a risk of PED. The presence of PED, regardless of duration of intubation, increased the rates of pneumonia, length of stay in the ICU and hospital, and healthcare expenditure.